(3GdSQGL GdefjQ aj GdEYGfI Ydi eYQaI HYV eYGfi cdGe QHfG GdMcje GdNHjQs - (3eMeO Hf CMeO GdTQHjfj, TeS GdOjf ; GdNWjH GdTQHjfj,J (B977 (3g` s ((3eMeO GdPgHi Hf SdjeGf GdbdYi s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdSdGe CeG HYO ai Chd YGe JSYeGFI hGMO hSJjf Ke SCdfi HYO Pdc LeGYI ef CUMGHi GdeNdUjf Cf CLYd dge JaSjQkG hSWkG Hjf GdWhjd Gdeeed hGdbUjQ GdeNd s
(3BNQgG (B:s
(3BNQ JaSjQ ShQI GdJhHI s
(3HOC JCdjaI SfI (B961(3g` hGfJgi efg SfI (B968(3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJ BjGJ GdcJGH GdYRjR s
(3hCSeGA GdSh QHGdMeQI s
(3YdjgG Jedc HGSe eMeO GdTjHi aGJM HjJ Gddg GdMQGe hYHO Gddg Hf YeQ Hf jMji s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs